2004
DOI: 10.1111/j.0742-2822.2004.02177.x
|View full text |Cite
|
Sign up to set email alerts
|

Infected Cardiac Myxoma

Abstract: Infected cardiac myxomas are extremely rare with only forty cases described in the literature. We report a case of an infected cardiac myxoma that presented in a manner similar to bacterial endocarditis. Our case is the first to be diagnosed using previously defined criteria, and is unusual in that transesophageal echocardiography was required to make the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…These systemic symptoms in myxoma, anemia, and raised ESR could be due to the systemic effects of interleukin 6, the cytokine implicated in generating a generalized inflammatory response in patients with myxomas, with levels decreasing after tumor excision [1, 12, 13], then criteria have been proposed by Revankar and Clark [14] to aid in the diagnosis of infected myxoma and they stated that the diagnosis is certain in the presence of myxoma documented by histology, and microorganisms observed in the sample, or a positive blood cultures and evidence of inflammation in the sample. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These systemic symptoms in myxoma, anemia, and raised ESR could be due to the systemic effects of interleukin 6, the cytokine implicated in generating a generalized inflammatory response in patients with myxomas, with levels decreasing after tumor excision [1, 12, 13], then criteria have been proposed by Revankar and Clark [14] to aid in the diagnosis of infected myxoma and they stated that the diagnosis is certain in the presence of myxoma documented by histology, and microorganisms observed in the sample, or a positive blood cultures and evidence of inflammation in the sample. …”
Section: Discussionmentioning
confidence: 99%
“…Myxomas are the most common primary tumors of the heart in adults, which have an estimated incidence of 0.5 per million population per year [1]. …”
Section: Introductionmentioning
confidence: 99%
“…Though transthoracic echocardiography is less invasive and presents an excellent sensitivity (up to 95%) in detecting myxomas, the diagnostic success using transesophageal echocardiography approaches 100% [25]. Nevertheless, recently a case of an infected cardiac myxoma has been reported, where transesophageal echocardiography was required in order to make the diagnosis [26]. The diagnosis of infected atrial myxoma is usually safely made when the microorganism can be isolated and the presence of an atrial myxoma, which naturally provides a nidus for infection, is demonstrated [27].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac myxoma is one of the primary intracardiac tumours. It accounts for 0.5 per million population per year [1]. It is a histologically benign tumour with a high risk of embolism due to its friable and gelatinous nature [2].…”
Section: Introductionmentioning
confidence: 99%